Burnout Rates Amongst General Orthopaedic Surgeons and Subspecialists. Issue 4 (22nd October 2020) - Nugent, Robert; Gaston, Tara E.; Markowitz, Michael; Daniel, Joseph N.; Cheesman, Quincy
Category: Other Introduction/Purpose: Burnout affects physicians in a multitude of ways, resulting in low levels of personal accomplishment (PA), depersonalization (DP), and high emotional exhaustion (EE). Overall, burnout has a direct impact on physician well-being and can negatively impact personal relationships, contribute to drug or alcohol use, and result in reduced outcomes in the work field. Although orthopaedic surgeon burnout rates of up to 50-60% have been reported, there have been no studies comparing burnout rates by orthopaedic subspecialty. The primary goal of this study is to examine the prevalence of burnout amongst orthopedic generalists and subspecialists. Given that a multitude of factors may contribute to burnout, a secondary goal is to identify trends in demographic data that may contribute to burnout. Methods: This was a multicenter, cross-sectional study conducted from March 2019 through December 2019 involving 149 orthopaedic surgeons with all orthopaedic subspecialties represented. The survey utilized an abbreviated 12-item Maslach Burnout Inventory - Human Services Survey (aMBI-HSS) to assess burnout. The aMBI-HSS consisted of three subcategories; PA, DP, and EE, each of which represented their own burnout score. Depression was also assessed in order to identify any correlation to increased burnout. Finally, independent factors, including demographics, personal characteristics, professional characteristics, and family life/spousal support were collected to assess how they contributed to burnout. Univariate and bivariate regression was performed to identify independent variables for multivariate regression analysis. Three separate generalized linear regressions were then performed to assess which independent factors led to an increase or decrease in the EE, DP, or PA burnout scores. Results: Mean burnout amongst all respondents was 62.29%, with 16.7% screening positive for depression. Oncology (100%), Sports Medicine (67.70%), and Trauma (62.50%) were the three specialties with highest burnout. In contrast, lowest burnout rates were seen in Shoulder and Elbow (50.0%), Pediatrics (51.6%), and Foot and Ankle (53.8%). Trauma (50.0%), Oncology (40.0%), and General (20.0%) had the highest rates of depression, while Shoulder and Elbow (0.00%), Spine (0.00%), and Sports Medicine (6.5%) had the lowest rates of depression. Independent factors associated with increased risk of burnout included Oncology subspecialty, older age, and increased debt. Contrarily, independent factors associated with decreased burnout were more years in practice, more hours worked per week, more time spent with family and close friends, work environment satisfaction, and home life satisfaction. Conclusion: Burnout is a growing problem amongst physicians. This study sought to determine which orthopaedic subspecialties had the highest rates of burnout and depression, while identifying any secondary contributing factors. Our study found that orthopaedic Trauma and Oncology had the highest rates of burnout and depression. Additionally, older age and higher debt load contributed to an increased rate of burnout and depression. As this is only a small representation of the orthopaedic surgical community, larger studies are necessary to help further understand burnout and elucidate effective treatment options for orthopaedic surgeons.